Exercise Induced Left Bundle Branch Block Treated with Cardiac Rehabilitation: A Case Report and a Review of the Literature - Nathan S. Anderson; Alexies Ramirez; Ahmad Slim; Jamil Malik (Case Reports in Vascular Medicine)
Exercise induced bundle branch block is a rare observation in exercise testing, accounting for 0.5 percent of exercise tests. The best treatment of this condition and its association with coronary disease remain unclear. We describe a case associated with normal coronary arteries which was successfully treated with exercise training. While this treatment has been used previously, our case has a longer followup than previously reported and demonstrates that the treatment is not durable in the absence of continued exercise.